2010
DOI: 10.4314/biokem.v18i2.56409
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary studies on ethanol production from <i>Garcinia kola</i> (bitter kola) pod: Effect of sacharification and different treatments on ethanol yield

Abstract: A study on yeast fermentation of bitter kola pod( agricultural waste) was carried out using dried active bakers' yeast (Saccharomyces cerevisiae)and brewer's yeast (Saccharomyces carlsbergensis) Effects of saccharification using Aspergillus niger and different treatments on the waste as they relate to the optimization of the ethanol production were investigated. The reducing sugar in the waste was increased after 24-48 hours of sacharification using Aspergillus niger, fresh bitter kola waste recorded 4.4 -8.0g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Itelima et al [6] stated that the ethanol yield obtained from plantain peels, cassava peels, and potato peels increases gradually from the first day to the seventh day of incubation with pineapple peels given up to 8.34% (v/v) yield of ethanol. Bukola et al [25] reported that biter kola fermented with baker's yeast could yield up to 2.16% (v/v) ethanol.…”
Section: Factors and Interactive Effects On Fermentationmentioning
confidence: 99%
“…Itelima et al [6] stated that the ethanol yield obtained from plantain peels, cassava peels, and potato peels increases gradually from the first day to the seventh day of incubation with pineapple peels given up to 8.34% (v/v) yield of ethanol. Bukola et al [25] reported that biter kola fermented with baker's yeast could yield up to 2.16% (v/v) ethanol.…”
Section: Factors and Interactive Effects On Fermentationmentioning
confidence: 99%